Penataan Kawasan Kota Lama Banyumas Terkait Manajemen Proyek: Penataan Kawasan Kota Lama Banyumas Terkait Manajemen Proyek (Universitas Wijayakusuma Purwokerto, 2024)
The area arrangement was carried out in the Bale Adipati Mrapat (pendapa) complex and Banyumas District as a cultural creative space (Cultural and Creative Park). The regional planning also targets the arrangement of public green open spaces, namely the Old City Square, which becomes a network of cultural and creative spaces. In other parts, the area will also beautify with pedestrian arrangements, street furniture, vegetation and landscaping. The area arrangement includes a Core Zone covering an area of ​​7 Ha, a Buffer Zone covering an area of ​​23.6 Ha, and a Development Zone covering an area of ​​172.7 Ha. From the series of project activities that have been implemented, it can be concluded that supervision of the Banyumas Old City Area Arrangement has been carried out. The results of the implementation are the weekly progress of the realization of the progress of the plan. If there is a delay, a solution or effort must be found. Then problems related to the quality and quantity of work, both material quality and building structure quality, are resolved by carrying out material testing and testing structural samples and their dimensions. Keywords : Earthquake, Building Construction, Earthquake Resistant Buildings